Annealing Effect on Optical properties of (As0.5Se0.5 doped with 1% Te) thin films - Rusul Adnan Al-Wardy (College of Pharmacy / Mustansiriyah University, 2018)
this work, the study of optical properties of (As0.5Se0.5 doped with 1% Te) thin films which prepared by thermal vacuum evaporation on glass bases at (R.T) with (100±20)nm thickness deposition rate (1.6nm/s) and study effect of annealing at temperatures (Ta) (348,398,448)K for time (30min) on these properties. The X-ray diffraction technique showed that all prepared films are amorphous in structure at room temperature and annealing films at (348, 398, 448)K. The transmittance spectra of the prepared films falls within a wavelength range (500-1100) nm, and increasing the annealing temperature leads to a decreased in  transmission, increased absorption coefficient, and shift of the absorption edge towards low photon energies. The optical measurements showed that the prepared films had an allowed indirect optical energy gap and were found to decrease with the increase of (Ta) within the range (R.T, 348,398,448) K. As indicated by the tails of the localized states, it was observed that they increased by increasing (Ta).